POTENSI BEBERAPA JENIS RUMPUT LAUT DI ACEH (STUDI KASUS: SKRINING FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN) - Adean Mayasri (Lantanida Journal, 2021)
One of the sea potentials in Aceh is seaweed. Seaweed contains secondary metabolites and antioxidants that are very well consumed because it can act as an antidote/protector from the free radicals. This study aimed to determine the secondary metabolite content and antioxidant activity of seaweed in Aceh.The seaweed that has been macerated then screened for phytochemicals and tested for antioxidant activity by using the DPPH method. The seaweed species found were Gracillaria verrucosa, Sargassum sp., and Chaetomorpha antennina. The results of this study indicated that Gracillaria verrucosa, Sargassum sp., and Chaetomorpha antennina seaweeds were contained by alkaloids and steroids. Flavonoid and saponins were only detected in the types of seaweed Gracillaria verrucosa and Sargassum sp. It was also found that the higher the concentration of the extract, the higher the percentage of IC50 against free radicals. The Sargassum sp. has a stable percentage of inhibition at a 2-10 ppm concentration, so it is recommended in this study to be considered cultivated in Aceh.